2009
DOI: 10.1902/jop.2009.080385
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Serum Interleukin (IL)‐6 and Gingival Crevicular Fluid of IL‐1β and Prostaglandin E2 Among Non‐Smoking Subjects With Gingivitis and Type 2 Diabetes

Abstract: Type 2 diabetes may increase the host inflammatory response to oral biofilm, which, in turn, may exacerbate preconditions associated with gingivitis in susceptible individuals. Furthermore, systemic inflammation, as demonstrated by the increased level of serum IL-6, is associated with BGI gingivitis among non-smoking patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 31 publications
1
40
1
Order By: Relevance
“…One study [33] showed the possibility that high levels of IL-6 in GCF indicate disease activity. Another study suggested that IL-6 is a key mediator that orchestrates the transition from acute to chronic inflammation and is elevated in periodontitis [34]. In the present study, our data showed that the mean level of IL-8 was significantly higher in diseased sites as compared to healthy sites.…”
Section: Discussionsupporting
confidence: 61%
“…One study [33] showed the possibility that high levels of IL-6 in GCF indicate disease activity. Another study suggested that IL-6 is a key mediator that orchestrates the transition from acute to chronic inflammation and is elevated in periodontitis [34]. In the present study, our data showed that the mean level of IL-8 was significantly higher in diseased sites as compared to healthy sites.…”
Section: Discussionsupporting
confidence: 61%
“…Most reports focus on chronic periodontitis in diabetes, but a limited number include gingivitis (Andriankaja et al 2009) and aggressive periodontitis (Davies et al 2011). The majority are cross-sectional studies and are designed to assess whether diabetes quantitatively or qualitatively influences the cytokine profile of patients with periodontal disease.…”
Section: Cytokines and Adipokinesmentioning
confidence: 99%
“…Our recent findings showed that sIL-6R levels in gingival crevicular fluid (GCF) of inflamed sites are significantly higher than in the healthy sites in periodontitis patients [7]. Importantly, it has been reported that both IL-1β and IL-6 levels in GCF were significantly elevated in diabetic patients [8,9]. Although synergistic effects of these cytokines may induce the severe periodontitis in diabetic patients, the relationship of diabetic conditions such as high glucose (HG) to the cytokine cascades are not fully understood.…”
Section: Introductionmentioning
confidence: 97%